2021
DOI: 10.3389/fnagi.2021.753210
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Triggering Receptor Expressed on Myeloid Cells 2 From Cerebrospinal Fluid in Sleep Disorders Related to Parkinson’s Disease

Abstract: Background: Triggering receptor expressed on myeloid cells 2 (TREM2) is a microglial receptor exclusively expressed in the central nervous system (CNS). It contributes to abnormal protein aggregation in neurodegenerative disorders, but its role in Parkinson’s disease (PD) is still unclear.Methods: In this case-control study, we measured the concentration of the soluble fragment of TREM2 (sTREM2) in PD patients, evaluated their sleep conditions by the PD sleep scale (PDSS), and analyzed the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…This indicates that serum sTREM2 has the potential to be a biomarker for MCI in OSA patients. These results were similar to previous studies ( Suárez-Calvet et al, 2016a , b ; Bekris et al, 2018 ; Ohara et al, 2019 ; Tanaka et al, 2019 ; Weber et al, 2020 ; Mo et al, 2021 ), although most tested sTREM2 levels in the CSF. In dementia and MCI, microglia in the central nervous system are activated and expression of TREM2 increases, with release of sTREM2 into the CSF.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This indicates that serum sTREM2 has the potential to be a biomarker for MCI in OSA patients. These results were similar to previous studies ( Suárez-Calvet et al, 2016a , b ; Bekris et al, 2018 ; Ohara et al, 2019 ; Tanaka et al, 2019 ; Weber et al, 2020 ; Mo et al, 2021 ), although most tested sTREM2 levels in the CSF. In dementia and MCI, microglia in the central nervous system are activated and expression of TREM2 increases, with release of sTREM2 into the CSF.…”
Section: Discussionsupporting
confidence: 92%
“…It is a hot topic that sTREM2 may be a potential biomarker or therapeutic target for cognitive impairment caused by various diseases ( Suárez-Calvet et al, 2016a , b ; Ohara et al, 2019 ; Tanaka et al, 2019 ; Weber et al, 2020 ; Mo et al, 2021 ). However, little is known about the relationship between sTREM2 and OSA or OSA-related cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the neuroinflammation in the SN induced by MPTP and rotenone, it may be necessary to detect the expression of soluble triggering receptor expressed on myeloid cells 2 (TREM2) in future studies, since soluble TREM2 in the cerebrospinal fluid (CSF) has been revealed to be a biomarker of neurodegeneration and glial activation in Alzheimer's disease ( 70 ). In several recent studies, soluble TREM2 in CSF has been reported as a potential biomarker of neuronal injury in Parkinson's disease ( 71 73 ).…”
Section: Discussionmentioning
confidence: 99%